Quality Analysis and Comprehensive Evaluation of Cistanche deserticola from Different Origins in China - Haimin LIU; Yan ZHAO; Xinmiao YU; Leiqing PAN; Lijun SONG (Shipin gongye ke-ji, 2023)
The present study aims at clarifying the quality differences of Cistanche deserticola (CD) from different areas. The contents of bioactive compounds extracted from different parts (root, middle and top stems) and their antioxidant activities were comparatively analyzed. The results showed that the contents and antioxidant activities of bioactive components were significantly affected by origins and parts. The samples from the southern Tengger desert (D) showed high concentrations of total polyphenols (17.66 mg GAE/g DW) and verbascoside (6.98 mg/g DW). These compounds showed high scavenging abilities against ABTS+ (IC50=1.48 mg/mL) and DPPH (IC50=0.38 mg/mL) free radical. Samples from the southern Gurbantunggut desert (E) showed the highest content of total flavonoids (16.58 mg RE/g DW). The highest content of total triterpenoid appeared in the sample from Badangirin desert (A) (18.63 mg OAE/g DW). Samples from the Gurbantunggut desert (F) had polysaccharides and procyanidins at levels of 31.18 and 4.71 mg PCE/g DW, respectively. The samples from the northern Tengger desert (C) had the highest echinoside content (17.75 mg/g DW) and hydroxyl radical scavenging ability (IC50=3.05 mg/mL). Three principal components were extracted by principal component analysis (PCA) with a cumulative variance contribution rate of 85.43%. Through hierarchical cluster analysis (HCA), the samples were divided into three groups. The four producing areas (A, B, C and D) of the first and second groups were distributed in Inner Mongolia and Gansu, and the comprehensive score was the top four. The results of this study would provide a theoretical basis for quality evaluation, product development and standardization of Cistanche deserticola in China.